Preparation and utilization of compost and implication for selected crop productivity: The case of Guagusa Shikudad District, Northwest Ethiopia - Gebeyehu, Lakachew Ayenew; Mekonen, Addisu Dagnaw; Fentie, Ayalneh Yedem (Ethiopian Journal of Social Sciences, 2025)
The deterioration of soil fertility is a significant issue in Ethiopia's agricultural sector. Organic fertilizers, particularly compost, can enhance soil fertility; however, compost preparation and utilization remain limited. This study aimed to identify the determinants of compost preparation and its implications for crop productivity in Guagusa Shikudad Disctict. Using a cross-sectional research design, data were collected from 124 households through surveys and interviews with agricultural experts. Quantitative data were analyzed using descriptive and inferential statistics including t-tests, one way ANOVA, Chi-square test, and binary logistic regression modeling. The results indicated that factors such as age, education, composting materials, farmer perception, economic status, extension services, farming experience, family size, and farm size significantly influenced compost preparation and utilization. The binary logistic regression model identified positive determinants (age, education, input availability, perception, economic level, extension support, farming experience, and family size) and a negative determinant (farm size). This variation was tested using a one-way ANOVA, yielding a statistically significant result (p < 0.05), which indicates a significant difference between users and non-users of compost. The results, moreover, indicate that compost utilization significantly enhances crop production and productivity. It is recommended that the district’s agricultural office and stakeholders promote compost preparation and utilization among smallholder farmers through continuous capacity building and extension services. Keywords: Adoption, Compost utilization, Crop productivity, Farming experience,  Farm size, Guagusa  Shikudad district